Green sustainable process for chemical and environmental engineering and science. - Inamuddin, 1980-; Boddula, Rajender; Asiri, Abdullah M. (Elsevier, 2020)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Sustainable Organic Synthesis provides an in-depth overview in the area of organic, pharmaceutical, engineering and environmental sciences, with a focus on the purification and extraction of fine chemicals, alternative green solvents, medicinal, analytical drugs, and bioactive compounds utilizing green chemistry protocols. It also focuses on the nanocatalysis, biocatalysis, solvent-free, recyclable organocatalysis, solid-supported reagents, heterogeneous polymer reusable catalysis, and CO2 conversion to commercial chemicals, utilizing industrial strategies such as flow-reactor, microwave, ultrasonics, ball-mill, photochemical and electrochemical methods. --